Electrodynamics of Dipolar Beads in an Electrophoretic Spherical Cavity - Lean, M.H.; V ̈olkel A.R. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The transient dynamics of dipolar beads in an electrophoretic spherical cavity presents an interesting phenomenon, because it captures the interplay of electrophoretics, particle dynamics, and tribology. The problem geometry is described by a dipolar bead immersed in a polarized fluid within the cavity. Switching bias voltages are applied to induce both translational and rotational motion of the bead. This paper details a model of coupled phenomena which employs ODE’s to describe the bead dynamics, integral equations for the field solution, and particle simulation for the bipolar migrations. Special focus is given to the impact of confinement and gravitational force on the bead dynamics.